Formative computer based assessment in diagram based domains - Bligh, Brett (2007)
This research argues that the formative assessment of student coursework in free-form, diagram-based domains can be automated using CBA techniques in a way which is both feasible and useful. Formative assessment is that form of assessment in which the objective is to assist the process of learning undertaken by the student. The primary deliverable associated with formative assessment is feedback. CBA courseware provides facilities to implement the full lifecycle of an exercise through an integrated, online system. This research demonstrates that CBA offers unique opportunities for student learning through formative assessment, including allowing students to correct their solutions over a larger number of submissions than it would be feasible to allow within the context of traditional assessment forms. The approach to research involves two main phases. The first phase involves designing and implementing an assessment course using the CourseMarker / DATsys CBA system. This system, in common with may other examples of CBA courseware, was intended primarily to conduct summative assessment. The benefits and limitations of the system are identified. The second phase identifies three extensions to the architecture which encapsulate the difference in requirements between summative assessment and formative assessment, presents a design for the extensions, documents their implementation as extensions to the CourseMarker / DATsys architecture and evaluates their contribution. The three extensions are novel extensions for free-form CBA which allow the assessment of the aesthetic layout of student diagrams, the marking of student solutions where multiple model solutions are acceptable and the prioritisation and truncation of feedback prior to its presentation to the student. Evaluation results indicate that the student learning process can be assisted through formative assessment which is automated using CBA courseware. The students learn through an iterative process in which feedback upon a submitted student coursework solution is used by the student to improve their solution, after which they may re-submit and receive further feedback.